Green Synthesis of Zinc Oxide Nanoparticles with Psidium cattleianum Leaves Extracts as Reducing Agent: Influence of Extraction Method on Physicochemical and Biological Activities - Christian Israel Padilla-Hernández; Jorge Manuel Silva-Jara; Martha Reyes-Becerril; Abril Fonseca-García; Luis Miguel Anaya-Esparza; Paulo Roberto Orozco-Sánchez; Juan José Rivera-Valdés; Mireille López-Orozco; Carlos Arnulfo Velázquez-Carriles; María Esther Macías-Rodríguez (Physchem, 2025)
This work successfully synthesized green zinc oxide nanoparticles using extracts from strawberry guava leaves (Psidium cattleianum Sabine). Additionally, the reducing effect of the antioxidant extracts obtained through traditional techniques, such as infusion and maceration, was studied and compared against an emerging unconventional technology like ultrasound assisted extraction. Regarding the physical and chemical characteristics, it was found that all three systems were confined within a wavelength range of 357 to 370 nm (UV-vis) and sizes from 60 to 140 nm for the ultrasound-assisted nanoparticles (SEM), corroborated with DLS (134 ± 60 nm). Through X-ray diffraction, the hexagonal wurtzite structure was elucidated, and it was observed that ultrasound favored a higher percentage of crystallinity (98%) compared to the infusion (84%) and maceration (72%). This could be correlated with different functional groups via FTIR and with thermal events associated with thermogravimetric curves, where the total biomass weight loss was lower for nanoparticles using ultrasound extract (6.25%), followed by maceration (15.55%) and infusion (18.01%) extracts. Furthermore, these nanostructures were evaluated against clinically relevant pathogens, including Salmonella enteritidis, Staphylococcus aureus, Escherichia coli O157:H7, and Pseudomonas aeruginosa, assessing bacterial growth inhibition using the microdilution technique, and achieving inhibitions of 75%. Biofilm activity was evaluated through Congo red and crystal violet assays, where ultrasound-derived NPs proved to be good inhibitors for all pathogens. Finally, the toxicity of the nanoparticles was analyzed against peripheral blood leukocytes from goats as well as on the 3 T3-L1 cell line used in anti-obesity assays; the nanoparticles proved to be suitable in all concentrations reaching around 100% cell viability, positioning them as good candidates for diverse industrial applications that align with the principles of green chemistry towards a circular economy.